PENINGKATAN KEMAMPUAN PEMAHAMAN DAN REPRESENTASI MATEMATIS SISWA SMA MELALUI STRATEGI PREVIEW-QUESTION-READ-REFLECT-RECITE-REVIEW - Mulyati Mulyati (Department of Mathematics Education, UIN Sunan Gunung Djati Bandung, West Java, Indonesia, 2016)
The study based on a lack of mathematical comprehension and representation. To overcome this, do research using preview-question-read-reflect-recite-review (PQ4R) strategy learning. This study looks at the enhancement of mathematical comprehension and representation ability among students who study mathematics with PQ4R strategy learning and conventional learning in terms of overall and category knowledge of prior mathematics students (high, medium, low). This study was quasi-experimental. The study design used was Nonequivalent Control Group Design using purposive sampling technique. The population in this study were senior high school students in Indramayu Academic Year 2012/2013. Research samples were senior students of class X. Instruments used in the study in the form of tests prior knowledge of mathematics, mathematical comprehension ability test, mathematical representation ability test, observations and questionnaires. The data were analyzed quantitatively and qualitatively. The quantitative analysis performed using independent sample t-test, and Two Way Anova test. The results showed that, (1) enhancement the mathematical comprehension dan representation ability PQ4R strategy learning students get better than students who received conventional learning in terms of overall and category knowledge of prior mathematics students; (2) there is significant interaction between learning and mathematical prior knowledge toward student’s mathematical comprehension and mathematical representation ability.